2010
DOI: 10.1039/c002843f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structure of mono-, bi- and trimetallic amine-bis(phenolate) cobalt(ii) complexes

Abstract: A series of cobalt(II) amine-bis(phenolate) complexes has been prepared and characterized. The protonated tripodal tetradentate ligand precursors; dimethylaminoethylamino-N,N-bis(2-methylene-4-tert-butyl-6-methylphenol),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 122 publications
3
39
0
Order By: Relevance
“…Absorptions around 240 nm are observed in the spectra of unmetalated ligand precursors but the absorptions around 280 nm are also observed in (amine)bis(phenolato) complexes not containing acac ligands. [17,78,85] Two absorptions between 340-550 nm are assigned as charge-transfer transitions from the ligand-to-metal (LMCT). The high energy bands around 340 nm arise from the transitions between the p π orbital of the phenolato oxygen and the half-filled d 3 .…”
Section: Electronic Absorption Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Absorptions around 240 nm are observed in the spectra of unmetalated ligand precursors but the absorptions around 280 nm are also observed in (amine)bis(phenolato) complexes not containing acac ligands. [17,78,85] Two absorptions between 340-550 nm are assigned as charge-transfer transitions from the ligand-to-metal (LMCT). The high energy bands around 340 nm arise from the transitions between the p π orbital of the phenolato oxygen and the half-filled d 3 .…”
Section: Electronic Absorption Datamentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Also, group 3 and lanthanide metal complexes of these ligands have been effective as catalysts or initiators for ring-opening polymerization of lactide and ε-caprolactone. [11][12][13][14][15][16] By comparison, there has been limited use of (amine)bis(phenolato) ligands with the first row late transition metals, [17][18][19][20][21][22][23][24] whereas the chemistry of monoanionic phenoxytriamine ligands with these metals is far more developed. [25][26][27][28][29][30][31][32][33][34][35] We are interested in the development of new inexpensive, non-…”
Section: Introductionmentioning
confidence: 99%
“…The [Co 2 BPP] complex exhibits an irreversible oxidation wave at 1.09 V, which can be ascribed to phenol oxidation, in agreement with the literature. [27] A second wave is observed at -0.53 V, also leading to a slight increase in the absorption bands of the complex at 250 and 315 nm (Supporting Information). This wave is consistent with the reduction of the Co III centers and the occurrence of pronounced changes in the coordination sphere (e.g., due to acetate release, Jahn-Teller effect) can be responsible for its irreversible character.…”
Section: Resultsmentioning
confidence: 92%
“…Cobalt(II) complexes, including 3, were prepared according to literature procedures [16]. Co(III) complexes were prepared via oxidation using AgNO3 or AgO3SCF3.…”
Section: Synthesis and Characterization Of Cobalt Complexesmentioning
confidence: 99%
“…A range of bifunctional cobalt-salen complexes have been reported that under the appropriate conditions either copolymerize or form cyclic carbonates from propylene oxide and carbon dioxide [12][13][14][15]. We have recently reported a series of well-characterized Co(II) complexes [16]. Given the precedent for carbon dioxide fixation using cobalt complexes of N,O-ligands, herein, we report our investigation of amine-phenolato Co(II) and Co(III) complexes, Fig.…”
Section: Introductionmentioning
confidence: 99%